EFFECT OF THE SMOKING ON CARDIOVASCULAR RESPONSES TO SUBMAXIMAL EXERCISE IN YOUNG WOMEN (Fiep Bulletin - online, 2015)
According to the World Health Organization (WHO) smoking is the chief, single avoidable cause of death in the whole world. Cigarette smoking affects the cardio-respiratory function thus reduceing the capacity of physical exercise. The objective of the present study was to verify the effect of the tobacco smoking on cardiovascular responses to graded submaximal physical exercise among sedentary female smokers. Systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) were measured noninvasively in young, non-smoking women (NSW, n=7) and smoking women (SW, n=7) at rest, during the accomplishment of submaximal bicycle ergometric test and recovery period. At rest, DBP and HR were higher in the SW group (75 ± 2 mmHg and 85 ± 12 bpm) when compared to the NSW group (67 ± 5 mmHg and 73 ± 5 bpm). During exercise, SBP and HR increased in the studied groups. DBP was higher in the SW group (~15%) in relation to the NSW group in all periods of exercise training. During the recovery period both DBP and HR were higher in the SW group when compared to the NSW group. These results show that young, smoking women present alterations in hemodynamic parameters at rest and in response to submaximal exercise.
Keywords: Tobacco; ergometric test; women.